Shaking table tests on reinforced concrete frames without and with passive control systems. - Dolce, Mauro (Earthquake engineering & structural dynamics.)
An extensive experimental program of shaking table tests on reduced scale structural models was carried out within the activities of the MANSIDE project, for the development of new seismic isolation and energy dissipation devices based on shape memory alloys (SMAs). The aim of the experimental program was to compare the behaviour of structures endowed with innovative SMA-based devices to the behaviour of conventional structures and of structures endowed with currently used passsive control systems. This paper presents a comprehensive overview of the main results of the shaking table tests carried out on the models with and without special braces. Two different types of energy dissipating and recentring braces have been considered to enhance the seismic performances of the tested model. They are based on the hysteretic properties of steel elements and on the superelastic properties of SMAs, respectively. The addition of passive control braces in the reinforced frame resulted in significant benefits on the overall seismic behaviour. The seismic intensity producing structural collapse was considerably raised, interstorey drifts and shear forces in columns were drastically reduced.